Membangun Brand Loyalty melalui Brand Experience dan Brand Image: Peran Mediasi Brand Trust (Studi pada Konsumen Produk Wardah di Semarang) - Irly Anoti; Mulyana (Lembaga Yasin AlSys, 2026)
Although the relationships among brand experience, brand image, brand trust, and brand loyalty have been widely examined, studies on the mediating role of brand trust among consumers of Wardah products in Semarang City remain limited and have yielded inconsistent findings. This study aimed to analyse the effects of brand experience and brand image on brand loyalty through brand trust. This study employed a quantitative approach with an explanatory research design. A total of 96 respondents were selected using purposive sampling. Data were collected through a Likert-scale questionnaire and analysed using multiple linear regression and the Sobel test with the assistance of IBM SPSS Statistics 26. The results showed that brand experience had a positive and significant effect on brand trust and brand loyalty. Brand image had a positive and significant effect on brand trust but had no significant direct effect on brand loyalty. Brand trust had a positive and significant effect on brand loyalty and was found to mediate the effects of brand experience and brand image on brand loyalty. These findings confirm that brand trust plays an important role in bridging the effects of brand experience and brand image on the formation of consumer loyalty. This study provides a theoretical contribution to the development of brand management literature and practical implications for Wardah and other cosmetics companies in designing strategies focused on enhancing brand experience, strengthening brand image, and building consumer trust. Future research may extend the model by incorporating other variables, such as customer satisfaction, brand love, and customer engagement, as well as broadening the research objects and geographical areas.